Model and Analysis of Photovoltaic Modules with Irradiation and Temperature Variations using Simulation Technology: Model dan Analisis Modul Photovoltaic dengan Variasi Iradiasi dan Temperatur menggunakan Teknologi Simulasi - Rahmaniar, Rahmaniar; Khairul, Khairul; Junaidi, Agus; Sari, Debby Kaumala (Universitas Muhammadiyah Sidoarjo, 2023)
This article discusses the modeling and analysis of Photovoltaic (PV) modules with irradiation and temperature variations using simulation technology. Modeling is carried out on solar modules through the p-n junction principle, a PV module model with temperature independence of photocurrent sources, diode saturation currents, and series resistances based on the Shockley diode equation. The photovoltaic process of solar radiation, PV cells convert a portion of the photovoltaic potential directly into electricity with I-V and P-V output characteristics. Electromagnetic radiation from the sun's energy is converted into electricity through the photovoltaic effect. The photovoltaic module simulation process with Matlab/Simulink, is carried out to observe the performance through the I-V and P-V characteristics of the solar module. The model, which is developed in a user-friendly manner using the Simulink block, shows the results of the PV characteristics when irradiation increases, the output current increases and the output voltage also increases. This results in a net increase in power output with increased irradiation at constant temperature.